A comparison of double clip angle shear connections to shear tab connections in industrial applications - Martin, Brandi Nichole (Kansas State University, 2017)
In structural steel connection design, simple shear connections are one of the most common connection types utilized. The industry, especially from the side of the engineer, tends to lean toward using Double Clip Angle Connections as the default standard for simple shear connections. A double clip angle connection is a connection consisting of two angles transferring the shear forces from one member to the next either through bolts or welds. The design of Double Clip Angle Connections is efficient and the connections themselves are easy to fabricate. However, benefits to utilizing other types of shear connections exist. Many of these benefits are seen in the fabrication shop or during erection and construction. This is especially true of single shear plate or shear tab connections when applied to open structure design. Shear tab connections consist of a single plate that transfers the shear forces from one member to the next with bolts or with welds. The design of shear tab connections can be a more involved process than the design of double clip angles. Sometimes the shear plate or shear tab has to be longer than is typical. This is called an extended shear plate connection. These extended shear plates can bring other variables into the design that typically don’t occur with Double Clip Angle Connections such as bending of the plate or the need for multiple bolt columns. However, with proper planning and detailing, the benefits and savings experienced in the fabrication or construction phase may outweigh what can be seen as a more laborious design task. The purpose of this report is to identify the possible benefits achieved in using each of these connections, highlight the differences in the design approach for each, and use a study model to compare the outcome of using one connection over another in the design of a typical open structure. Double clip angles are typically the most efficient approach when speed of design and simplicity of fabrication are the desired outcomes. However, shear plate or shear tab connections have the potential to provide safer erection alternatives and materials savings if used in appropriate ways and with the right applications.
Keywords: Shear Connections; Double Clip Angle Connections; Shear tab connections; Structural steel connection design